THE IMPLEMENTATION OF VIDEO PROJECT TO IMPROVE STUDENTS’ SPEAKING SKILL - Mustika, Yeni; Dashela , Tarina (Jurnal Ilmiah Spectral, 2025)
This research used a video project to improve students speaking skills. There were found that the students of Bina Sarana University especially in the first semester of 36 students had difficulties in speaking activities. The students did not have self-confidence since English was not their first language. The students were afraid of making mistakes. They had trouble pronouncing the word or sentence. They were lack of vocabulary mastery which led them to be reluctant to speak up about their ideas.  The classroom action research method with two cycles was used in this research. The observation and measurement techniques were used as the technique of collecting data. The observation checklists, field notes, interviews, and tests were used as the instruments for collecting data. The result showed that the use of video projects could help the teacher to improve the student's speaking skills effectively. It creates a fun, memorable, and enjoyable learning activity. Video projects help the students develop their motivation during the teaching and learning process.